The politics of health care reform in Central and Eastern Europe: the case of the Czech Republic - Ovseiko, P (2009)
This thesis examines the political process of health care reform between 1989 and 1998 in the most advanced sizable political economy in Central and Eastern Europe (CEE) – the Czech Republic. Its aim is to explain the political process bringing about post-Communist health policy change and stimulate new debates on welfare state transformation in CEE. The thesis challenges the conventional view that post-Communist health care reform in CEE was designed and implemented to improve the health status of the people, as desired by the people themselves. I suggest that this is a dangerous over-rationalisation, and argue that post-Communist health care reform in the Czech Republic was the by-product of haphazard democratic political struggle between emerging elites for power and economic resources. The thesis employs the analytical narrative method to describe and analyse the actors, institutions, ideas and history behind the health policy change. The analysis is informed by welfare state theory, elite theory, interest group politics theory, the assumptions of methodological individualism and rational choice theory, and Schumpeter’s doctrine of democracy. Its focus is on the interests of health policy actors and how they interacted within an unhinged, but fast-consolidating, institutional framework. The results demonstrate that, while historical legacies and liberal ideas featured prominently in the rhetoric accompanying health policy change, in Realpolitik, these were merely the disposable, instrumental devices of opportunistic, self-interested elites. The resultant explanation of health policy change stresses the primacy of agency over structure and formulates four important mechanisms of health policy change: opportunism, tinkering, enterprise, and elitism. In conclusion, the relevance of major welfare state theories to the given case is assessed and implications for welfare state research in CEE are drawn.